Spatial heterogeneity of soil properties of recreational areas of Volgograd - O. A. Gordienko; R. N. Balkushkin (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
The article presents the developed soil maps and maps of spatial variability of soil properties (pH, total salt and carbonate content, organic carbon, density) in some recreational areas of Volgograd. The anthropogenic soils in the studied recreational areas include various urbostratozems (Urbic Technosols (Transportic)), Ekranic Technosols (Transportic), as well as quasizems (Phaeozems (Tehnic)), among the agrogenic ones – accumulation-carbonate agrozems (Cambisols (Aric, Protocalcic). Natural soils are represented by light and dark humus soils, chestnut soils, solonetz, as well as stratozems and psammozems. According to the data of isolinear mapping, it was found that acid-alkaline properties of soils of green zones vary from slightly alkaline to alkaline depending on the soil horizon and anthropogenic load. The mapping did not reveal salinization of the upper 0–30 cm layer. Values of organic carbon vary greatly (1–10%) and are conditioned by the presence or absence of meliorative artificial layers, as well as by the character of territory use. The content of calcium carbonates in the upper 30 cm is small and varies from 0.7 to 5%. It is established that the physical properties (density) directly depend on the level of anthropogenic load, increasing in footpaths and lawns. Spatial assessment of the properties of urban soils is important for identifying areas with an excess or on the contrary – low content of certain chemical and physical indicators for the planning of landscaping and gardening of urban areas.